Historical and recent advances in genetic and genomic research on gummy stem blight in watermelon - Prachi Bista; Glennescia Tenner; Lewis Brooks; Frank Mrema; Muhammad Riaz; Abdus Sobhan; Bed Prakash Bhatta (Academia Molecular Biology and Genomics)
Gummy stem blight (GSB) is one of the most important fungal diseases of cucurbits (watermelons, cucumbers, melons, pumpkin, and squash) in the United States. GSB is caused by the fungal pathogen Didymella bryoniae (syn. Stagonosporopsis cucurbitacearum), causing a significant loss in the yield and quality of crops. Currently, farmers must apply multiple rounds of fungicides to control GSB, which further adds to the overall cost of watermelon production. There are no commercial watermelon varieties with GSB resistance. Examining the genetic and molecular factors behind watermelon resistance to GSB will provide valuable information to inform future breeding efforts aimed at developing GSB-resistant watermelon varieties. Recent advances in genome sequencing, gene expression profiles, next-generation sequencing, marker-assisted selection, and breeding have led to a much deeper understanding of the molecular dynamics between watermelon and the gummy stem blight pathogen, leading to the development of more resistant cultivars as well as better disease management strategies. In this review paper, we discuss the biology of the GSB pathogen, history of the GSB disease, genomic resources of watermelon and the GSB pathogen, historic and recent genetic inheritance studies on GSB, and quantitative trait loci mapping to better understand GSB resistance in watermelon. This review paper lays the foundation and justification for upcoming research focused on resolving the current challenges in gummy stem blight studies and crop improvement.